Pengembangan Sistem Pakar Coping Stress Berdasarkan Tipe Kepribadian Menggunakan Metode Certainty Factor - Julianti, Annisa A; Tenriawaru, Andi; Hamundu, Ferdinan Murni; Tohamba, Riansyah; Efendi, Ilham Julian (Jurusan Sistem Informasi Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to develop an expert system for stress management that integrates individual personality types using the Certainty Factor (CF) method. Stress management refers to an individual’s response to stress, influenced by their personality type, which determines the effectiveness of coping strategies. The CF method quantifies the confidence level in the decisions made by the system. The expert system identifies personality types based on user responses to a questionnaire or test, subsequently providing tailored stress management recommendations. The system was developed using the Waterfall methodology, incorporating CF analysis, Black Box Testing, accuracy evaluation, and User Acceptance Testing (UAT). The system accommodates four personality types and 94 traits, allowing users to select traits they identify with, each carrying a weight to determine personality classification. Black Box Testing confirmed the functionality of all features. Accuracy analysis yielded a result of 62.16%, reflecting the system’s moderate precision in diagnosing personality types. UAT results scored 87.18%, categorized as “good,” indicating strong user acceptance and satisfaction. This system demonstrates the potential for assisting individuals in managing stress effectively by aligning strategies with their personality profiles.